Addressing uncertainty in mouthing-mediated ingestion of chemicals on indoor surfaces, objects, and dust. (January 2021) - Li, Li; Hughes, Lauren; Arnot, Jon A.
Highlights: Mouthing-mediated chemical ingestion is explored using a novel mechanistic model. Chemicals found in hand wipes are mainly from dust transfer, whereas those ingested are mainly residues. Increasing dust loadings on surfaces may lower mouthing-mediated ingestion of low-volatility chemicals. Mouthing-mediated ingestion initially increases and then plateaus with more frequent contact with surfaces. More frequent handwashing lowers mouthing-mediated ingestion, more prominent for relatively volatile chemicals. Abstract: In indoor environments, humans ingest chemicals present as surface residues and bound to settled particles (dust), through mouthing hands (hand-to-mouth transfer) and objects (object-to-mouth transfer). Here, we introduce a novel modeling approach in support of systematic investigation into the mouthing-mediated ingestion of chemicals present in indoor environments. This model explicitly considers the indoor dynamics of dust and chemicals, building on mechanistic links with physicochemical properties of chemicals, features of the indoor environment, and human activity patterns. The evaluation of this model demonstrates that it satisfactorily reproduces chemical hand loadings and exposure data reported in the literature. We then use the evaluated model to investigate the response of mouthing-mediated ingestion to chemical partitioning between the gas phase and solid phases, expressed as the octanol–air partition coefficient ( K OA ). Assuming a unit emission rate to the indoor environment, we find that low-volatility chemicals (with a K OA greater than 10 9 ) are more efficiently enriched in hand skin, resulting in higher mouthing-mediated ingestion than other compounds. For individuals living in a room with a typical level of dustiness, more than half of the chemical mass found in their hands comes from dust transfer, whereas more than half of the chemical mass ingested is the fraction present as residues on hands. We also use the new model to explore how the mouthing-mediated ingestion of chemicals is dependent on factors describing the indoor environment and human behavior. The model predicts that less frequent cleaning leads to higher accumulation of dust on indoor surfaces, thereby transferring more chemicals to hands and mouth in each contact. Introducing more dust into the room, but maintaining the same cleanup frequency, increases the dustiness of indoor surfaces, which promotes the transfer of relatively volatile chemicals (with a K OA lower than 10 9 ) to hands and mouth but decreases the transfer of chemicals with low volatility. More frequent hand contact with indoor surfaces increases both the hand loading and mouthing-mediated ingestion of chemicals, but the increases are more remarkable for adults than children because the higher surface contact frequency of children "saturates" hand loadings. An increase in handwashing frequency lowers the hand loading and mouthing-mediated ingestion of chemicals and this mitigating process is more prominent for relatively volatile chemicals. The new evaluated modeling approach can facilitate the prediction of mouthing-mediated ingestion for various age groups and the model predictions can be used to aid future fate and (bio)monitoring studies focusing on indoor contamination.